Inquiry into life - Mader, Sylvia S (McGraw-Hill, 2000)
Includes bibliographical references and index; 36 chapters: the study of life I; the molecules of cells; cell structure and function; mem brane structure and function; cell division; metabolism: energy and enxymes; cellular resoiration; photosynthesis;...